Comparative study of one-bid versus two-bid auctions - Radosveta Ivanova-Stenzel; Doron Sonsino (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
We compare the standard one-bid first price auction to a corresponding two-bid first price auction where each buyer may place two bids: a high bid and a low one and the winner pays his low bid if this was higher than all other bids. We characterize the equilibria of the two mechanisms and prove some results on the ranking of revenues and expected utilities across the two mechanisms for the symmetric case. We show that subjects in a computerized experiment prefer the two-bid auction over the one-bid auction when given the possibility of choosing among the two and we claim that this and other aspects of subjects' behavior conform to the equilibrium predictions for risk-averse subjects. We also report some discrepancies between the experimental results and the equilibrium predictions and provide some alternative explanations to the observed behavior.
urn:nbn:de:kobv:11-10050399
Keywords: D44; C91; 330; experiments; sealed-bid private-value auctions